Similarity solution of stagnation-point flow and heat transfer of a micropolar fluid towards a horizontal permeable exponentially elongating sheet with radiation, heat production/ immersion - Parthiban, R.; Palani, G. (Zielona Góra: Uniwersytet Zielonogórski)
The current study aims to explore stagnation spot flow of a micropolar fluid about a plain linear exponentially expanding penetrable surface in the incidence of radiation and in-house heat production/immersion. Through similarity mapping, the mathematical modeling statements are transformed to ODE`s and numerical results are found by shooting techniques.
Keywords: exponentially stretching sheet; heat spring/drop; micropolar fluid; radiation; suction/injection